Robustness of the western United States power grid under edge attack strategies due to cascading failures - Wang, Jian-Wei; Rong, Li-Li (Safety science, 2011)
► The effect of attacks depends on the local characteristics of a breakdown edge. ► Don’t ignore the importance of the edges with the lowest load in cascading failure. ► Rational allocation of network resources can enhance network robustness. Power systems are the basic support of modern infrastructures and protecting them from random failures or intentional attacks is an active topic of research in safety science. This paper is motivated by the following two related problems about cascading failures on power grids: efficient edge attack strategies and lower cost protections on edges. Applying the recent cascading model by adopting a local load redistribution rule, where the initial load of an edge ij is ( k i k j ) θ with k i and k j being the degrees of the nodes connected by the edge, we investigate the performance of the power grid of the western United States subject to three intentional attacks. Simulation results show that the effects of different attacks for the network robustness against cascading failures have close relations with the tunable parameter θ. Particularly, the attack on the edges with the lower load in the case of θ < 1.4 can result in larger cascading failures than the one on the edges with the higher load. In addition, compared with the other two attacks, a new attack, i.e., removing the edges with the smallest proportion between the total capacities of the neighboring edges of and the capacity of the attacked edge, usually are prone to trigger cascading failures over the US power grid. Our findings will be not only helpful to protect the key edges selected effectively to avoid cascading-failure-induced disasters, but also useful in the design of high-robustness and low-cost infrastructure networks.